The Influence of Self-Tapping on Anxiety During Primary Menstrual Cramps among Nursing Students - Lismidiati, Wiwin; Fidyasanti, Neni; Nurkhasanah, Nurkhasanah (Jurusan Keperawatan FIKES UNSOED, 2019)
ABSTRACTBackground: Menstruation is a sign of puberty for female adolescents. The common menstrual disorder experienced by adolescent is called painful menstruation (primary dysmenorrhea). Primary dysmenorrhea triggers both physical and psychological symptoms. One of the psychological impacts is anxiety. Self-tapping is a non-pharmacological therapy which can reduce anxiety.Aim: To figure out the effect of self tapping toward anxiety level among nursing students experiencing menstrual cramps.Methods: This study was a quasy-experimental research with non equivalent pretest-posttest with control group. The total 60 respondents were divided into intervention and control group with 30 respondents each. Self tapping was practiced in intervention group, meanwhile deep breath was performed in control group. The instruments to measure anxiety were anxiety screening questionare and Hamilton Anxiety Rating Scale (HARS). Wilcoxon statistical test was applied to compare the level of anxiety before and after the treatment in both groups. Besides, Mann Whitney satistical test was used to compare the effectiveness of both treatments in reducing the anxiety level in each group.Results: The anxiety mean score of the intervention group decreased from 24,63 to 16,03 after self tapping (?=8,6; p=0,000), while the anxiety mean score of the control group decreased from 23,5 to 17,73 after the implementation of deep breath technique (?=5,77; p=0,000). There was a significant difference between self tapping and deep breath technique in reducing anxiety level (p-value=0.006). Conclusion: Self tapping indeed has impact towards anxiety level among nursing students experiencing menstrual cramps.